Proposed Unesco Social Science Programme for 1977-78. (International Social Science Journal)
The article presents information on proposed UNESCO Social Science Programme for 1977-78. The draft programme and budget for UNESCO, which is now being circulated to Member States and will be discussed and voted at the nineteenth General Conference to take place in Nairobi in October-November 1976, contains detailed proposals for a greatly strengthened social science programme. For the first time since 1966, the social sciences are to have independent administrative status again, as they did between 1946, when UNESCO was founded, and ten years ago. In the past decade, the Social Science Department has in fact been part of the Sector for Social Sciences, Humanities and Culture, its programme, budget and staff being significantly smaller than that for culture. The draft programme and budget is presented under eight headings, corresponding to the constituent divisions of the new Social Science Sector, set up on April 1, 1976. In addition, it is anticipated that operational activities to a total of just over $1 million will be financed from sources such as the United Nations Development Programme or the United Nations Fund for Drug Abuse Control. A regional Field Office for Asia and Oceania is also to be maintained.